2023
DOI: 10.1210/jendso/bvad036
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbances Across a Woman's Lifespan: What Is the Role of Reproductive Hormones?

Abstract: Fluctuations of reproductive hormones are associated with various forms of sleep disturbances and specific sleep disorders, e.g. insomnia or sleep-disordered breathing, across different stages of reproductive ageing. During the menstrual cycle, sleep is particularly disrupted during the late luteal phase as demonstrated by both objective and subjective measurements of sleep. Progesterone and its metabolites generally have sleep promoting effects. A steep decline in progesterone, e.g. during the late luteal pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 141 publications
(175 reference statements)
0
4
0
Order By: Relevance
“…Premenopausal women have been diagnosed with higher incidence of insomnia than postmenopausal women [40,41]. Significant age, waist circumference, and BMI differences in the current study may also play a role in such variation.…”
Section: Smrmentioning
confidence: 58%
“…Premenopausal women have been diagnosed with higher incidence of insomnia than postmenopausal women [40,41]. Significant age, waist circumference, and BMI differences in the current study may also play a role in such variation.…”
Section: Smrmentioning
confidence: 58%
“…Thus, interventions for insomnia are essential for addressing presenteeism—when workers attend work but have diminished efficiency and productivity and undermine workplace safety. The literature suggests that sex differences play a role: Among women who experience premenstrual syndrome experience, over 70% experience an impact in their daily life as a result of insomnia and other physical symptoms; 25 insomnia during pregnancy increases the risks for premature birth and depression; 26 among postmenopausal women, 35–60% experience sleep disorder; 27 women aged in their 40s or 50s experience higher production of orexin as a result of a decline in estrogen levels amid diminished ovarian function; 28 , 29 among women who experience a menopause-related decline in progesterone production (which stimulates the respiratory center, increasing breathing rate), 30 sleep apnea syndrome is approximately as prevalent as it is among men (whereas among other women, it is less prevalent than among men). 31 While our study revealed no significant sex-based differences, women outnumbered men at the initial visit and at >1 year, and the mean age, 44, suggested that many patients would have been experiencing menopause; thus, sex should be taken into account during medical checks.…”
Section: Discussionmentioning
confidence: 99%
“…Gender emerges as a crucial determinant in shaping sleep behavior, influencing sleep architecture, and modulating the prevalence and manifestation of sleep disorders ( Haufe and Leeners, 2023 ). Several factors are involved in reducing sleep quality and increasing sleep disorders among women.…”
Section: Discussionmentioning
confidence: 99%